2021
DOI: 10.1002/chem.202102684
|View full text |Cite
|
Sign up to set email alerts
|

Host‐Guest Complexation Between Cyclodextrins and Hybrid Hexavanadates: What are the Driving Forces?

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…The first explanations for such a striking phenomenon were given based on the investigations of supramolecular interactions involving POMs with model nonionic substrates such as micelles, cyclodextrins, or polymers. The desolvation process of POMs through supramolecular interactions with these nonionic units leads to robust supramolecular aggregates in water. The release of the “high energy” hydration shell around the POMs corresponds to a highly favorable thermodynamic process that is featured by an enthalpy gain and an entropy penalty. ,, In other words, the hydration properties of POMs often represent the main contributor among the conglomerate of weak attractive interactions capable of maintaining supramolecular assemblies.…”
Section: Poms As Electrocatalytically Active Multiredox Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…The first explanations for such a striking phenomenon were given based on the investigations of supramolecular interactions involving POMs with model nonionic substrates such as micelles, cyclodextrins, or polymers. The desolvation process of POMs through supramolecular interactions with these nonionic units leads to robust supramolecular aggregates in water. The release of the “high energy” hydration shell around the POMs corresponds to a highly favorable thermodynamic process that is featured by an enthalpy gain and an entropy penalty. ,, In other words, the hydration properties of POMs often represent the main contributor among the conglomerate of weak attractive interactions capable of maintaining supramolecular assemblies.…”
Section: Poms As Electrocatalytically Active Multiredox Centersmentioning
confidence: 99%
“…The release of the "high energy" hydration shell around the POMs corresponds to a highly favorable thermodynamic process that is featured by an enthalpy gain and an entropy penalty. 45,145,146 In other words, the hydration properties of POMs often represent the main contributor among the conglomerate of weak attractive interactions capable of maintaining supramolecular assemblies.…”
Section: Cluster Containing Polyoxometalatesmentioning
confidence: 99%
“…Herein, we demonstrate the on-surface molecular recognition, charge stabilization, and multistate switching of Lindqvist-type hexavanadate single-POM anions (hereafter referred to as [V 6 –(OH) 2 ] 2– ) by “filtering out” bulky alkyl ammonium countercations (commonly applied in the synthesis of POMs) during their deposition on surfaces. The principles of supramolecular chemistry are employed for assembling the POM anions with macrocyclic organic matrices, such as cyclodextrins (CDs). , The individual components of the host–guest complexes studied herein are shown in Figure . Our study paves the way for the controlled adsorption of POMs and stabilization of their charge states by decoupling them electronically from the substrate surface (weak-coupling regime).…”
mentioning
confidence: 99%
“…The study is inspired by ground-breaking works by Cadot, Haouas, Falaise and co-workers who reported spectacular supramolecular host–guest aggregates based on POMs (tungstates and molybdates) and γ-cyclodextrin: the authors reported that the systems are stabilized by a combination of hydrogen bonding and chaotropic effects. 44–46…”
mentioning
confidence: 99%
“…The study is inspired by groundbreaking works by Cadot, Haouas, Falaise and co-workers who reported spectacular supramolecular host-guest aggregates based on POMs (tungstates and molybdates) and gcyclodextrin: the authors reported that the systems are stabilized by a combination of hydrogen bonding and chaotropic effects. [44][45][46] Here, we decided to study POV-based host-guest formation using the macrocyclic aza-crownether cyclen (1,4,7,10tetraazacyclododecane, C 8 H 20 N 4 ) as guest. We chose cyclen as it has similar diameter and similar C 4 -symmetry to {V 12 }, features four independent protonation sites 47 and offers an ideal balance between structural rigidity (due to the ethylene bridges) and adaptability (due to the absence of bulky substituents).…”
mentioning
confidence: 99%